Macrophages in homeostatic immune function - Jantsch, Jonathan; Binger, Katrina J.; Müller, Dominik N.; Titze, Jens (Frontiers in Physiology, 2014)
Macrophages are not only involved in inflammatory and anti-infective processes, but also play an important role in maintaining tissue homeostasis. In this review, we summarize recent evidence investigating the role of macrophages in controlling angiogenesis, metabolism and salt and water balance. Particularly, we summarize the importance of macrophage tonicity enhancer binding protein (TonEBP, also termed nuclear factor of activated T-cells 5 [NFAT5]) expression in the regulation of salt and water homeostasis. Further understanding of homeostatic macrophage function may lead to new therapeutic approaches to treat ischemia, hypertension and metabolic disorders.